Bar-HRM: A reliable and fast method for species identification of ginseng (Panax ginseng, Panax notoginseng, Talinum paniculatum and Phytolacca Americana) - Maslin Osathanunkul (2020)
Copyright © 2019 Osathanunkul and Madesis. Background. Korean ginseng has long been famous and is one of the most well known forms of ginseng. The root of plants in the genus Panax is commonly recognized as ginseng. Different Panax species of ginseng root have been used as treatments. Although many other herbs are called ginseng, they do not contain the active compounds of ginsenosides. In Thailand, we have Thai ginseng which is of course not one of Panax species. Thai ginseng is the root from Talinum paniculatum and, due to its morphological root similarity, it is almost impossible to differentiate between them. Also, another plant species, Phytollacca americana, has significantly similar root morphology to real ginseng but its seeds and root are poisonous. Misunderstanding what true ginseng is compared to others could endanger lives and cause financial loss by buying inferior products. Methods. DNA barcoding combination with High Resolution Melting (called Bar-HRM)was used for species discrimination of the Panax ginseng and others. Five regions included ITS2, matK, psbA-trnH and rbcL were evaluated in the analyses. Results. The ITS2 region was found to be the most suitable primers for the analysis. The melting profile from the HRM analyses using the chosen ITS2 primers showed that Korean ginseng (Panax ginseng) could be discriminated from other Penax species. Also, other ginseng species with morphological similarity could be easily distinguished from the true ginseng. The developed Bar-HRM method poses a great potential in ginseng species discrimination and thus could be also useful in ginseng authentication.